Measuring ROI for Training and Development for Leadership Role Interventions in Online Travel Agencies (OTA) - Shaikh, Naazim Zahir (Digital Repository of Theses - SSBM Geneva, 2025)
This dissertation explores the impact of leadership training programs on organizational performance within Online Travel Agencies (OTAs). As OTAs operate in a dynamic and competitive environment, effective leadership fosters innovation, enhances customer service, and improves team collaboration. The research evaluates the influence of leadership training on employee engagement, team dynamics, employee performance, and customer service efficiency to identify actionable strategies for improving these programs. The study employs a mixed-methods approach, gathering data from 211 respondents across diverse geographical regions and organizational sizes. The research analyzes metrics such as motivation, job satisfaction, productivity, and customer satisfaction using structured questionnaires and organizational records. Statistical methods, including paired t-tests and chi-square analyses, alongside the Phillips ROI Methodology, quantify the training's tangible and intangible impacts. Key findings reveal that leadership training significantly boosts employee engagement, with 64% to 78% of respondents reporting improved motivation, alignment with organizational goals, and job satisfaction. Enhanced team collaboration and communication were observed, with 56% to 61% of respondents acknowledging better teamwork, trust, and conflict resolution. Employee performance metrics, including productivity, task efficiency, and work quality, improved for 51% to 61% of participants, while customer service efficiency saw notable gains, with 51% to 64% reporting improved responsiveness, satisfaction, and loyalty. Despite these positive outcomes, neutral responses ranging from 19% to 37% indicate training relevance and practical application gaps. The study recommends tailored content, real-world scenarios, and regular follow-ups to address these challenges and ensure sustained improvements. This research highlights the critical role of leadership training in driving organizational success in OTAs. By addressing identified gaps and leveraging tailored strategies, OTAs can develop a more engaged, collaborative, and high-performing workforce, ensuring long-term competitiveness in a rapidly evolving industry. The findings provide a foundation for future studies to refine leadership development practices across diverse organizational contexts.